2017
DOI: 10.1111/asj.12802
|View full text |Cite
|
Sign up to set email alerts
|

Survival of spray‐dried and free‐cells of potential probiotic Lactobacillus plantarum 564 in soft goat cheese

Abstract: A high viability of probiotics in food product, with a living cells threshold of 10 /cfu/g (colony-forming units/g) is a challenge to achieve in food production. Spray drying is an efficient and economic industrial method for probiotic bacterial preservation and its application in food products. In this study, the survival of free and spray-dried cells of potential probiotic strain Lactobacillus plantarum 564 after production and during 8 weeks of storage of soft acid coagulated goat cheese was investigated, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Obtained results indicate that optimal conditions were achieved during spray drying process. Similar results were obtained in our previous studies [ 23 , 29 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Obtained results indicate that optimal conditions were achieved during spray drying process. Similar results were obtained in our previous studies [ 23 , 29 ].…”
Section: Resultssupporting
confidence: 93%
“…salivarius strains with probiotic potential [ 47 , 48 ]. Our previous studies [ 29 ] demonstrated a high viability and survival rate of spray dried Lb. plantarum 564 cells while using a constant inlet air temperature of 170 °C and outlet temperature of 80 °C, indicating successful use of applied spray drying conditions as a method of bacterial preservation in the present research.…”
Section: Resultsmentioning
confidence: 99%
“…Radulović et al. () reported that the addition of Lactobacillus plantarum 564 (free‐ and spray‐dried cells) to soft goat cheese resulted in both great viability of the probiotic bacteria and sensory acceptance. These results suggest that spray‐dried Lb.…”
Section: Potential Beneficial and Nutritional Features Of Goat Milkmentioning
confidence: 99%
“…In fact, the probiotic goat cheese was well-accepted (flavor, appearance, texture, color, and global liking) by consumers, although the purchase intention was low. Radulović et al (2017) reported that the addition of Lactobacillus plantarum 564 (free-and spray-dried cells) to soft goat cheese resulted in both great viability of the probiotic bacteria and sensory acceptance. These results suggest that spray-dried Lb.…”
Section: Cheesementioning
confidence: 99%
“…Traditional cheeses are a potential pool of new LAB strains with desirable biological and metabolic properties such as: acidogenic activity, production of antimicrobial compounds, production of proteinases, and probiotic properties [ 18 , 19 , 20 ]. Among LAB, the genera Lactococcus and Enterococcus are most commonly used as adjunct cultures in different products to control foodborne pathogens or to improve product quality [ 17 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%